Indiana University and the world : a celebration of collaboration, 1890-2018 - O'Meara, Patrick (Indiana University Press, 2019)
This commitment to international engagement continues into Indiana University's third century, with the launch of Gateway offices in economically and culturally dynamic parts of the world, such as China, India, Germany, and Mexico.